2014
DOI: 10.1086/678511
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 13– and Interleukin 17A–Induced Pulmonary Hypertension Phenotype Due to Inhalation of Antigen and Fine Particles from Air Pollution

Abstract: Pulmonary hypertension has a marked detrimental effect on quality of life and life expectancy. In a mouse model of antigen-induced pulmonary arterial remodeling, we have recently shown that coexposure to urban ambient particulate matter (PM) significantly increased the thickening of the pulmonary arteries and also resulted in significantly increased right ventricular systolic pressures. Here we interrogate the mechanism and show that combined neutralization of interleukin 13 (IL-13) and IL-17A significantly am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 80 publications
(181 reference statements)
8
51
0
5
Order By: Relevance
“…All three markers were significantly increased by exposure to the antigen and PM 2.5 as expected [16] in wild type mice and also in B cell KO mice (Fig 5C–5E). Compared with wild type animals, B cell KO mice exposed to antigen and PM 2.5 had increased RELMβ expression in the lungs, that reached statistical significance in the group of B cell KO mice injected with antigen specific IgG1 (Fig 5D).…”
Section: Resultssupporting
confidence: 84%
“…All three markers were significantly increased by exposure to the antigen and PM 2.5 as expected [16] in wild type mice and also in B cell KO mice (Fig 5C–5E). Compared with wild type animals, B cell KO mice exposed to antigen and PM 2.5 had increased RELMβ expression in the lungs, that reached statistical significance in the group of B cell KO mice injected with antigen specific IgG1 (Fig 5D).…”
Section: Resultssupporting
confidence: 84%
“…15 However, blocking either the T H 2 or T H 17 pathway with anti–IL-13 or anti–IL-17 alone has been shown not to be sufficient for the treatment of allergic asthma because such treatment resulted in upregulation of the other pathway. 18 Similarly, a recent study by Park et al 34 demonstrated that coadministration of anti–IL-17 and anti–IL-13 reduced both T H 2 and T H 17 cell responses in the lung in an animal model of antigen-induced pulmonary arterial remodeling, whereas anti–IL-17 or anti–IL-13 alone resulted in upregulation of T H 2 or T H 17 downstream effector genes, respectively. Collectively, these reports imply that simultaneous targeting of both T H 2 and T H 17 cell responses would be a promising strategy for the treatment of allergic asthma, whereas targeting either pathway alone might be ineffective because of activation of the other pathway.…”
Section: Discussionmentioning
confidence: 88%
“…Die Blockierung von IL-13/IL-4 vermindert diese Läsion hoch signifikant [24,27]. IL-13 und IL-4-assoziierte Biomarker sind im Blut von einer Subgruppe von Patienten gefunden worden, die an einer systemischen Sklerose erkrankt sind [23,28].…”
Section: T-zell-assoziierte Zytokine Und Ph (Qabb 1a)unclassified
“…TGFβ kann von fast allen Zellen produziert werden und kann von vielen Zelltypen aktiviert werden. Genetische Modelle weisen ebenfalls auf die Rolle einer gestörten Th17/Treg-Balance und des veränderten Zusammenspiels der Th17-und Th2-Antwort [27]. Mäuse, die ein defektes BMPR2-Transgen exprimieren, haben eine veränderte Immunantwort [34,36,37] mit einem gestörten Gleichgewicht von TGFβ-Signalen [38].…”
Section: T-zell-assoziierte Zytokine Und Ph (Qabb 1a)unclassified
See 1 more Smart Citation